Trends of Millenial Generation Hijrah in Religious Maturity Perspective - Hikmayanti, Asri Nur; Rahmat, Munawar (International Journal Pedagogy of Social Studies, 2023)
The Hijrah trend has recently been prevalent among the millennial generation. This trend is more popular thanks to social media, which has become an important communication and information tool for today's people, especially millennials. The hijrah movement is a social phenomenon that marks the phase of the journey of the millennial generation who participates in animating the movement of Islamic studies in Indonesia. This movement has both positive and negative sides. On the positive side, the trend of hijrah shows Islamic nuances from the style of dress and da'wah language that adorns various social media lines. But on the negative side, the direction of hijrah became the beginning of a movement oriented towards a dogmatic understanding of religion and tended to become a new, different meaning. The Hijrah trend has metamorphosed into a lifestyle and further highlights the new shari'ah identity for the millennial generation. Based on this problem, it is necessary to study the Migration Trend of the Millennial Generation from the Perspective of religious maturity. The question is, how is the millennial generation's Hijrah Trend seen from spiritual maturity? The research method uses library research with reference sources in the form of articles in relevant journals and books because the problem to be studied is in the form of social phenomena.